“I-Do” Feminism Courtesy of Martha Stewart Weddings and HBC’s Vow To Wow Club: Inventing Modern Matrimonial Tradition with Glue Sticks and Cuisinart - Matrix, Sidney (Ethnologies, 2006)
This article examines the wedding gift registry as a newly invented tradition and part of the increasing commodification of everyday life and its rites of passage. The research involves both a deconstructive discursive analysis and a critique of the visual rhetoric in advertisements promoting registries for the newly engaged. To consider the cultural context within which marketing for wedding gift registries is proliferating, the author begins with the stories of two connected figures, both lifted from national newswires. Then she argues that the escalating trend of the wedding registry gains momentum because of its placement between these two conjoined images, namely: the spectre of the scandalous and hysterical “runaway bride” and her sister, the hip and paradoxical “I-Do Feminist.”